Perception of Malaysian consumers towards probiotics in fermented foods and their benefits to human health - Ida Muryany Md Yasin,; Nurul Dayana Zainudin, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Consumers demonstrated an increase in awareness and interest in food that are closely associated with health benefits. As such, consumers are interested in consuming probiotic products and foods. Probiotics are bacteria that offer various benefits to human health when consumed in sufficient quantities. Numerous probiotic products have been listed, including fermented foods that contain probiotics that are beneficial to human health. Hence, consumers should be aware of these products. This study aimed to analyze the knowledge and awareness of consumers about probiotics and their benefits to human health and to evaluate the perception of consumers towards probiotics in fermented foods based on the socio-demographic profiles. The questionnaire was developed using Google Forms and distributed through social media. The data was analyzed using SPSS software. 150 respondents were involved, but only 133 of the data were selected. Descriptive analysis was conducted to determine the frequency of data from the socio-demographic profiles. Meanwhile, statistical analyses using chi-square analysis was conducted to identify significant difference at p-value < 0.05 between consumers’ socio-demographic profile and their awareness, knowledge, and perceptions of probiotics and probiotics in fermented food. Overall, the survey indicated that consumers were well aware of, and had the knowledge and good perceptions towards probiotics and their presence in fermented foods.